2007
DOI: 10.1002/nur.20234
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the challenges of multidisciplinary responses to sexual assault victims: Sexual assault nurse examiner and victim advocacy programs

Abstract: The purpose of this study was to examine Sexual Assault Nurse Examiner (SANE) programs' relationships with victim advocacy organizations. A national telephone survey was conducted of randomly selected SANE programs, all of which served adults, and some of which also served adolescents and children. Nearly one-third of 231 participants reported that SANEs in their program had experienced conflicts related to roles and boundaries with victim advocacy organizations at some point during the program's history. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 29 publications
1
66
0
Order By: Relevance
“…In a national survey, Cole and Logan (2008) found that 80% of SANE program coordinators reported power struggles between advocates and nurses within their programs. Similarly, SANEs interviewed in four East Coast states reported that the advocates engage in power struggles by overstepping their boundaries.…”
mentioning
confidence: 98%
“…In a national survey, Cole and Logan (2008) found that 80% of SANE program coordinators reported power struggles between advocates and nurses within their programs. Similarly, SANEs interviewed in four East Coast states reported that the advocates engage in power struggles by overstepping their boundaries.…”
mentioning
confidence: 98%
“…Advocates may experience the coordination as particularly tenuous and insecure. Previous research has suggested that advocates are at a disadvantage because their role is often not a statutory obligation for communities, and as such advocates are guests in hospitals and police stations (Cole & Logan, 2008; Martin, 2005). Advocates may find that SART offers a more central position in the system response to rape.…”
Section: Discussionmentioning
confidence: 99%
“…Given that research on SARTs and rape response more generally suggests that conflict stems from role negotiation (Cole & Logan, 2008) and differing professional norms (Martin, 2005), this study focused on understanding the kinds of strategies that SART professionals adopt to help them negotiate professional boundaries. In particular, this study sought to answer the following questions: (a) What kinds of conflict management strategies are described by SART professionals?…”
Section: Understanding Team Conflict Management Strategiesmentioning
confidence: 99%
“…Previous studies have shown that the counselor's beliefs about therapeutic effectiveness can have a significant impact on treatment outcomes (Asay & Lambert, 1999;Austad, 2009;Gladding, 2009;Wampold, 2007). This is especially true in the case of childhood sexual abuse in that counselors (or other helping professionals such as nurses, physicians, law enforcement, and CPS) can have a significant impact on survivor treatment outcomes (Briere & Scott, 2006;Cole & Logan, 2008;Davis, 1984;Ginzberg et al, 2006;Muller et al, 2004). The literature has shown that counselor subtle attitudes and biases regarding childhood sexual abuse may have a deterring effect on survivors' willingness to initially disclose or explore issues of child sexual abuse in the therapeutic environment (Cole & Logan, 2008;Davis, 1984;Day et al, 2003).…”
Section: Impact Of Counseling On the Survivormentioning
confidence: 99%
“…This is especially true in the case of childhood sexual abuse in that counselors (or other helping professionals such as nurses, physicians, law enforcement, and CPS) can have a significant impact on survivor treatment outcomes (Briere & Scott, 2006;Cole & Logan, 2008;Davis, 1984;Ginzberg et al, 2006;Muller et al, 2004). The literature has shown that counselor subtle attitudes and biases regarding childhood sexual abuse may have a deterring effect on survivors' willingness to initially disclose or explore issues of child sexual abuse in the therapeutic environment (Cole & Logan, 2008;Davis, 1984;Day et al, 2003). If the survivor is unable to safely talk to the counselor about their abuse, resolution or therapeutic processing is unlikely to occur.…”
Section: Impact Of Counseling On the Survivormentioning
confidence: 99%